A amamentação sob a ótica das profissionais da saúde: saberes e práticas do processo - Godoi, Vanessa Cristina de (2015)
Being a woman today no longer means being or becoming a mother. Women today have the right to choose about your decisions, your lifestyle and especially about motherhood. By this bias, understanding of breastfeeding nowadays, involves when women: mother, wife, worker and citizen, seeking changes in accordance with the historical, social and cultural contexts. The decision to breastfeed woman is linked to her life story, the importance it attaches to this act, being a personal choice of certain women for their existence in the world, but she feels charged by society that values motherhood and see the practice of breastfeeding as a natural virtue, a divine, pure and universal gift. The displeasure is not always explicit by those who experience, it is not compatible to the mother of idealized profile. The biological aspects of breastfeeding overlaps the subjectivity of women and at the same time it claims to be free to choose, you must be prepared to charges imposed by society. It is noticed that the health professionals who hold knowledge about breastfeeding, whose main role assistance to nursing mothers and, from that, they become the protagonists in the success of this practice. But you should think at this health professional side as a woman, as a mother, and how is breastfeeding for them. Some mothers, even though health professionals may have difficulty to breastfeed, and these difficulties can be often underestimated before qualification. The objectives of this study were to understand the breastfeeding process from the standpoint of health professionals, to describe the experience of breastfeeding for health professionals and identify knowledge and practices involving breastfeeding by what was experienced during breastfeeding. A qualitative approach was used, based on interviews of 12 health professionals from different areas of training that had already gone through the breastfeeding experience and their children, who worked or have worked in the neonatal intensive care unit and rooming Holy House of Irati. Data were analyzed by content analysis, thematic modality, of which the following themes were extracted: Breastfeeding: a natural act or naturalized?; Weaving possibilities for the genre and practices of breastfeeding; The "sovereignty" of scientific knowledge and the maternal experience: entanglements; The consequences of Breastfeeding experiences in professional practice. We conclude that, although it relates to breastfeeding as something natural, aspects related to negative and unpleasant moments experienced by women during breastfeeding were highlighted by them in their speech, showing a different view of what has been touting the speeches in favor of breastfeeding. We also realize that breastfeeding for these women is often taken as an obligation, as a burden that carry the qualifications they possess, and the social determinants and gender. However, regardless of the experience was good or bad, health professionals changed their look for the mother.